(3JcedI TQM GdegPHs - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s; (3GdajQhRGHGOj GdTjQGRj , CHh ESMb EHQGgje Hf Ydj GdTjQGRj, CHh GSMGb , LeGd GdOjf,J (B476 (3g` s
(3ChdgG (B:s
(3HGH HjY GdeUQGg s
(3BNQgG (B:s
(3hgPG hGab eG UMMg Gdfhhj hGddg CYde hMSHfG Gddg hfYe Gdhcjd s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B51 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B68s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1912s
Keywords: (3Gdabg GdTGaYjs